2023
DOI: 10.3390/su15032197
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Fit Optimization and Effect Evaluation of a Female Wetsuit Based on Virtual Technology

Abstract: At present, the traditional mode of research and development for mass-produced wetsuits usually requires repeated sample making and try-on evaluation, and performance cannot be predicted, monitored and evaluated in real time; this can lead to problems including low material utilization and production efficiency. In this study, real human body static and dynamic measurements, material properties and structure data are applied through 3D software to build an accurate virtual model, and new wetsuits are designed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(15 reference statements)
0
0
0
Order By: Relevance
“…Many studies have concluded that the performance of the material is the pivotal factor influencing the comfort felt while wearing compression pants [1][2][3]. However, it is worth noting that well-designed and balanced pressure distribution can greatly enhance both the comfort and aesthetic appeal of these pants [4].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have concluded that the performance of the material is the pivotal factor influencing the comfort felt while wearing compression pants [1][2][3]. However, it is worth noting that well-designed and balanced pressure distribution can greatly enhance both the comfort and aesthetic appeal of these pants [4].…”
Section: Introductionmentioning
confidence: 99%